1983
DOI: 10.1002/ardp.19833161108
|View full text |Cite
|
Sign up to set email alerts
|

Nichtsteroidale Entzündungshemmer, 17. Mitt.1) 4.5‐Bis(4‐methoxyphenyl)‐2‐arylthio‐azole mit antiphlogistischer Wirkung

Abstract: Es werden die Synthesen von 4.5-Bis(4-methoxyphenyl)-2-arylthio-imidazolen, - Antiinflammatory Agents, XVII: 4.5-Bis-(4-methoxypbenyl)-2-(arylthio)azoles with Antiinfianunatory ActivityThe syntheses of 4,5-bis(4-methoxyphenyl)-2-(arylthio)imidazoles, -thiazoles and -oxazoles are described and their antiinflammatory activities are compared. Thioethers, sulfoxides, and sulfones of the phenyl, 4-fluorophenyl, and 2-thienyl derivatives were investigated. The oxazole derivatives show almost no antiphlogistic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Anti-inflammatory, analgesic, and antipyretic activities for some thiazolyl and benzothiazolyl derivatives are also known. 7,8 On the other hand, sulfonamides have a variety of biological activities such as antibacterial, [9][10][11] insulin releasing, 12 carbonic anhydrase inhibitory, 13,14 anti-inflammatory, 15 and antitumor 16 activities. These findings encouraged us to explore the synthesis of sulfonamides containing thiazole/benzothiazole moieties and to examine their antibacterial and antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory, analgesic, and antipyretic activities for some thiazolyl and benzothiazolyl derivatives are also known. 7,8 On the other hand, sulfonamides have a variety of biological activities such as antibacterial, [9][10][11] insulin releasing, 12 carbonic anhydrase inhibitory, 13,14 anti-inflammatory, 15 and antitumor 16 activities. These findings encouraged us to explore the synthesis of sulfonamides containing thiazole/benzothiazole moieties and to examine their antibacterial and antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the applicability of the approach to the thiazole derivatives, the results of prediction are compared to experimental data for some compounds from the set, studied as 3,4,5,6,7,8,9,10,11,12,14,15,17,18,19,20,26,27,28,29 non-steroid antiinflammatory (78 compounds); local anaesthetics (6 compounds); antioxidants (5 compounds) tests. These data are given in Table II. In the experiment the compound is considered as being active if its potency is no less than the potency of the appropriate reference drug (the experimental errors are taken into account).…”
Section: Resultsmentioning
confidence: 99%
“…Anti-inflammatory, analgesic, antipyretic activities for some thiazolyl and benzoisothiazolyl derivatives are also known [9,10]. The screening tests for these compounds have been chosen on the basis of certain researchers' purposes.…”
Section: Data Setmentioning
confidence: 99%
“…In our previous work, some of polycyclic hetero-system derivatives were studied as 5␣-reductase inhibitors, antiviral, anti-tumor [1], aromatase and quinone reductase-2 inhibitors for chemoprevention of cancer [2], anti-inflammatory, analgesic and antipyretic activities [3][4][5][6][7][8]. Recent studies have shown the synthesis of some new azole candidates as antimicrobial and anticancer agents [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%